Slavery, Slave Trade and Manumission in Gojjam, 1940s-1950s. - Ayenew Mammo Seyoum (PhD) (Cita Konsultindo Research Center, 2022)
Like in other African countries, in Ethiopia slavery and slave trade was practiced for centuries and had been an endemic for the society In this article I have made an attempt to bring out the efforts of different emperors, particularly Emperor Haile Sellassie’s period in order to regulate and prohibit slavery and slave trade in Ethiopia and to discuss the existence of the institutions and the practice until the 1950s. The attempt of the Ethiopian rulers to regulate or prohibit the slave trade in slaves failed owing to several reasons. Anyway, the most serious laws making the beginning of the end for the institution of slavery in Ethiopia came in the 1920s. In attempt to counter European criticism Ras Tafari issued an edict in 1923 and 1924 imposing heavy penalties on the slave trade without, however, abolishing the legal status of slavery itself. Later, Ethiopia became a signatory to the ‘Slavery Convention of 1926.’ The official policy of the Ethiopian government against the slave trade, however, did little to stop the regional war lords from continuing to raid the borderlands for slaves. The continuation of slave trading and slavery itself in Ethiopia into the 1930s, the involvement of the state in the trade and the continued use of slaves in the royal court were directly contrary to the public statements of Emperor Haile Sellassie I and the legal commitments of the Ethiopian state. Immediately after the evacuation of the Italian although Emperor Haile Sellassie made efforts to prohibit the trade in slaves, it continued to flourish. Even in 1942 he issued an edict imposing heavy punishment on those who involved either in capturing or kidnapping or selling slaves. Nonetheless, this does not mean that it came to an end. For this, I have discovered archival evidences in Debre Markos Administrative Office and Higher Court House of Eastern Gojjam Zone, and in Dangla and Metekel administrative offices. Accordingly, the archives I discovered have three categories: the first deals with people who were accused of catching, kidnapping and selling slaves on the basis of eye witness who punished from seven to twenty years of imprisonment. The second category is dealing with people who were accused of kidnapping and selling individuals as slaves for money but for lack of witness, who pardoned and set free. The third phase is connected with the people who after capturing and kidnapping individuals with intent to sell them to slavery but because of the absence of a purchaser, who treated them brutally. The sources are critically collected, scrutinize and analyzed and their validities are cross-checked one against the other. Finally, as a historical research, the paper is based on a systematic selection, collection and analysis of archival documents, manuscripts and secondary sources of both published and unpublished.